Fabrication of phyco-functionalized zinc oxide nanoparticles and their in vitro evaluation against bacteria and cancer cell line (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Macroalgae with innumerable metabolites are predominantly identified as potential organisms in industrial and pharmaceutical applications. Herein, an attempt was made to fabricate zinc oxide nanoparticles (ZnO NPs) using the aqueous extract of red macroalgae Kappaphycus alvarezii and evaluate its anti-tumor and anti-bacterial activities, in vitro. ZnO NPs was prepared via chemical reduction (C-ZnO NPs), for comparative analysis, and co-precipitation method with the extract (B-ZnO NPs). Chemical composition analyses, physical characterization by UV Spectrophotometer, Fourier Transform InfraRed (FTIR) spectroscopy, Energy Dispersive X-Ray Analysis (EDX) and Scanning Electron Microscopy (SEM) and anti-oxidant ability by DPPH assay were performed. Anti-microbial activity of the fabricated nanomaterials was performed against E. coli, Bacillus subtilis and Staphylococcus aureus. Cell toxicity study was carried out using MTT assay upon 3T3 and MCF-7 cell lines. The study resulted that the presence of phenolic content in the algal extract enhanced the biological activities of ZnO NPs at an optimized concentration of 100 mM. Total phenolic content was exa mined to be 83.73 mg gallic acid eq/g and the maximum efficiency of DPPH scavenging was revealed by the concentration of 51.99 mg/mL. Anti-bacterial effect of B-ZnO NPs demonstrated maximum efficiency at the concentrations of 800 µg/mL, 400 µg/mL and 600 µg/mL against Escherichia coli, Bacillus subtilis and Staphylococcus aureus respectively. The cell viability study denoted that the fabricated B-ZnO NPs were non-toxic towards 3T3 while significant cytotoxicity was observed against MCF-7 at an IC50 of 75 µg/mL at 48 h. In conclusion, the B-ZnO NPs was observed to be effective as both bactericidal and anti-cancerous nano-agent and considered further for pharmaceutical applications.